Peran Etos Kerja Kepala Madrasah dalam Meningkatkan Kompetensi Pedagogik Guru di Madrasah Aliyah Al Ishlah Sukadamai - Ahmad Harun Al Rasyid; Taqwatul Uliyah; Endang Ekowati (Departement of Mathematics Education, 2024)
Head of Madrasah in Working on the Educational Skill of Madrasah Aliyah Al Ishlah Sukadam Educators for the 2023/2024 Scholastic Year. The kind of examination utilized is enlightening subjective exploration, specifically an exploration methodology that produces spellbinding information as composed or verbally expressed words from individuals and entertainers noticed, coordinated from the singular's experience in general (all encompassing) without separating the individual and the association inside. variable however check it out. as a component of an entirety. In information assortment methods in this exploration, different procedures were utilized, to be specific meetings, perception and documentation. The information examination technique utilized in this exploration is subjective examination. In light of the discoveries of the examination and conversation, the exploration results can be presumed that the hard working attitude of the Head of Mama Al Ishlah Sukadam keeps on encountering critical improvement. Obviously a leap forward in something that prompts a profoundly imaginative improvement, works. To have the option to make progress, the Madarasah he leads should have a hard working attitude in light of difficult work, discipline, obligation, a feeling of satisfaction in their calling, the will or want to change designs. thinking for progress, efficiency, discernment, inventiveness, development, present day thinking, and critical thinking direction. Aside from that, there must likewise be components of sufficient educator ability, one of which is the instructor's academic capability who can handle understudies in the homeroom so that educating and learning exercises can be accomplished. runs well and makes outcome in the madrasah's vision and mission.